Iron deficiency in blood donors - Rodolfo Delfini Cançado; Carlos Sérgio Chiattone; Fausto Forin Alonso; Dante Mário Langhi Júnior; Rita de Cássia Silva Alves (São Paulo Medical Journal)
CONTEXT: Blood donation results in a substantial loss of iron (200 to 250 mg) at each bleeding procedure (425 to 475 ml) and subsequent mobilization of iron from body stores. Recent reports have shown that body iron reserves generally are small and iron depletion is more frequent in blood donors than in non-donors. OBJECTIVE: The aim of this study was to evaluate the frequency of iron deficiency in blood donors and to establish the frequency of iron deficiency in blood donors according to sex, whether they were first-time or multi-time donors, and the frequency of donations per year. DESIGN: From September 20 to October 5, 1999, three hundred blood donors from Santa Casa Hemocenter of São Paulo were studied. DIAGNOSTIC TESTS: Using a combination of biochemical measurements of iron status: serum iron, total iron-binding capacity, transferrin saturation index, serum ferritin and the erythrocyte indices. RESULTS: The frequency of iron deficiency in blood donors was 11.0%, of whom 5.5% (13/237) were male and 31.7% (20/63) female donors. The frequency of iron deficiency was higher in multi-time blood donors than in first-time blood donors, for male blood donors (7.6% versus 0.0%, P < 0.05) and female ones (41.5% versus 18.5%, P < 0.05). The frequency of iron deficiency found was higher among the male blood donors with three or more donations per year (P < 0.05) and among the female blood donors with two or more donations per year (P < 0.05). CONCLUSIONS: We conclude that blood donation is a very important factor for iron deficiency in blood donors, particularly in multi-time donors and especially in female donors. The high frequency of blood donors with iron deficiency found in this study suggests a need for a more accurate laboratory trial, as hemoglobin or hematocrit measurement alone is not sufficient for detecting and excluding blood donors with iron deficiency without anemia.